The Evaluation of Company X Internal Control Based on Coso - Atria Putri; Tubagus M. Yusuf Khudri (Budapest International Research and Critics University, 2022)
As many as 27.6% of the 370 MSMEs that showed an increase in sales during the COVID-19 pandemic were those who were able to implement digitalization. Online shopping is now the leading choice and the number has been increasing by around 30% in Indonesia. One of the shops that experienced an increase in sales during the pandemic is Company X, engaged in the beauty industry. Running this shop for more than four years, Company X's finance division only consists of the owner who has a medical background. Therefore, the purpose of this study is to help the company improve risk mitigation, internal control, and the performance of its revenue cycle. The approach uses a case study method, analyzed by collecting data through semi-structured interviews about the revenue cycle and then evaluated based on 17 COSO 2013 principles. The results of this study indicate that the company has carried out control efforts informally, but it is not adequate because it is not in accordance with COSO 2013 and SAK EMKM. Company X must establish written and formal documents related to SOPs, risk management, evidence of the results of actions, and conduct customer satisfaction surveys.